Pelatihan Manajemen Skit Untuk Jemaat Gereja Kristus Yesus Serpong - Gandadinata Thamrin (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2020)
Religious activities such as Christmas and Easter celebrations in the church often use drama performances in delivering spiritual messages to the congregation, spiritual messages in the form of short plays or called skits are more easily accepted by adults and children so that the messages conveyed can be absorbed by the whole church. This was felt to be a necessity for the church to prepare talented, skilled and skilled human resources (HR) in making this short drama so that the leaders and committee of the Church requested training from Pelita Harapan University, Karawaci to give a workshop on "Skit Management Planning and Training Strategy Training. for the Church of Christ Jesus, Serpong "as a provision for activists, administrators and Servants of God in the church in the form of Community Service Activities. This workshop was conducted at the request of the Creative Team of Christ Jesus Church Development to develop their abilities in making short dramas that can be used in service to all commissions both Sunday School, Youth and Youth Commission, Caleb Commission and the general congregation. Training is conducted every Saturday for 4 meetings. First meeting: discussing the basic theories and concepts of drama as a work of art as well as video examples relating to short plays. Second meeting: in the form of implementing strategy and management planning to make a short drama (skit). Furthermore, at the third and fourth meetings it is a direct practice that includes the director, acting, dance support and makeup techniques and stage layout. This activity was responded positively by the participants and supported by UPH LPPM. Participants have additional basic knowledge about skit management, planning, and strategies for making effective and efficient skits in church service. After training the students practice making short dramas according to the instructions given in church religious events.